Mechanical Parameters and Trajectory of Two Chinese Cervical Manipulations Compared by a Motion Capture System - Huang, Xuecheng; Lin, Dongxin; Liang, Zeyu; Deng, Yuping; He, Zaopeng; Wang, Mian; Tan, Jinchuan; Li, Yikai; Yang, Yang; Huang, Wenhua (Frontiers in Bioengineering and Biotechnology, 2021)
Objective: To compare the mechanical parameters and trajectory while operating the oblique pulling manipulation and the cervical rotation–traction manipulation. Methods: An experimental research measuring kinematics parameter and recording motion trajectories of two cervical manipulations were carried out. A total of 48 healthy volunteers participated in this study, who were randomly divided into two groups of 24 representing each of the two manipulations. A clinician performed two manipulations in two groups separately. A motion capture system was used to monitor and analyze kinematics parameters during the operation. Results: The two cervical manipulations have similar thrust time, displacement, mean velocity, max velocity, and max acceleration. There were no significant differences in active and passive amplitudes between the two cervical rotation manipulations. The thrust amplitudes of the oblique pulling manipulation and the cervical rotation–traction manipulation were 5.735 ± 3.041° and 2.142 ± 1.742°, respectively. The thrust amplitudes of the oblique pulling manipulation was significantly greater than that of the cervical rotation–traction manipulation (P < 0.001). Conclusion: Compared with the oblique pulling manipulation, the cervical rotation–traction manipulation has a less thrust amplitudes.